Learning Analytics: A Case Study of the Process of Design of Visualizations - Olmos, Martin; Corrin, Linda (Online Learning, 2012)
The ability to visualize student engagement and experience data provides valuable opportunities for learning support and curriculum design. With the rise of the use of learning analytics to provide “actionable intelligence” [1] on students’ learning, the challenge is to create visualisations of the data which are clear and useful to the intended audience. This process of finding the best way to visually represent data is often iterative, with many different designs being trialled before the final design is settled upon. This paper presents a case study of the process of refining a visualization of students’ learning experience data. In this case the aim was to create a visual representation of the continuity of care students were exposed to during a longitudinal placement as part of a medical degree. The process of visualization refinement is outlined as well as the lessons learnt along the way.